ANALISIS MODEL RESTRUKTURISASI KUERI DALAM MENGOPTIMASI WAKTU RESPONS EKSEKUSI DATA PADA BASIS DATA RELASIONAL MYSQL PHP 7.2.27 - Olivia Maria Inacio Tavares; Sartje Mala Rangkoly; Sarah Bunda Desi Bawan; Khifni Beyk Ahmad; Ema Utami; Muhammad Syukri Mustafa (Universitas Nusa Cendana, 2021)
Database is a collection of data that forming an information that useful for managers in an organization to facilitate data management process to become more effective and safely guarantee. A good database has fast and accurate response time performance in data execution processing. To manage the database, it requires a special language or query known as Structure Query Language (SQL). Increase need for fast information, will need a proper SQL as well. Therefore, through this research, a test analysis will be used to optimize the query response time in database management system commonly used today, namely the My Structured Query Language (MySQL) using PHP version of 7.2.27 relational database which will be tested on the Oebufu Village Aspiration and Information Service System (SELMA) that acessed from localhost panels with a total of 1000 test data records. The test is devoted to the effectiveness of using SELECT queries in calling and displaying data through restructuring the use of clauses. This study aims to help improve data management by providing the results of the comparative analysis of response times between the general query model and the optimized query results in order to determine the correct and efficient query structure. The result is proven by doing query optimization, it is found that the presentation of time optimization is significant, which is 78% much faster than the initial query, through this test it can be concluded that optimization plays an important role in streamlining the response time of database queries.